Pesantren Education Management: The Transformation of Religious Learning Culture in the Age of Disruption - Siti Halimah; Achmad Yusuf; Khamdan Safiudin (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2024)
In recent decades, technological disruption has brought significant changes to various aspects of life, including education. Amidst this development, Pesantren-based education, a traditional education model, faces significant challenges in maintaining its identity, especially in maintaining religious culture-based learning. This study focuses on the complex dynamics between Pesantren traditions and religious values and the impact of technological disruption in education management at various levels, such as Raudhatul Athfal, Madrasah Ibtidaiyah, Tsanawiyah, and Aliyah. As part of the approach to Pesantren-based education management, the aim is to uncover the transformation of religious culture learning in the era of disruption, which will then serve as the basis for creating a relevant and adaptive education model. The research method used is qualitative, with in-depth case studies conducted in several Pesantrens. This design is selected based on the phenomenon's complexity involving a combination of traditional and modern aspects in the transformation of religious learning. Data collection techniques involve participatory observation, in-depth interviews with Pesantren leaders, teachers, and students, and document analysis of Pesantren policies and curricula. The study results indicate the importance of developing an Islamic education model responsive to technological advances while maintaining the traditional values of Pesantrens. Integrating modern management, technology, and religious values produces relevant and adaptive education in technological disruption. This study provides an essential contribution to creating an inclusive, dynamic Islamic education that maintains the essence of religious values amidst the development of the times.